Effectivity of Health Education with Telenursing on the Self-care Ability of Coronary Artery Disease Patients: A Systematic Review - Leutualy, Vanny; Trisyany, Yanny; Nurlaeci, Nurlaeci (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Coronary artery disease (CAD) develops chronically and progressively, causes recurrence and premature death, so a good knowledge of changes in self-care behavior by patients is needed. Telenursing can be a medium for health education to allow patients to receive information and for nurses to follow up on health conditions without being obstructed by distance, place, time, and carried out sustainably. So far, telenursing has not been reviewed as a recent intervention to deliver education to CAD patients. AIM: This systematic review aimed to determine the effectiveness of health education interventions with telenursing on the self-care of CAD patients based on the implementation media. METHODS: Systematic reviews were conducted based on items found in CINAHL EBSCO, PubMed, ScienceDirect, and Google Scholar from 2008 to 2019. The combination of keywords used Indonesian and English language. All articles were assessed using the Joanna Briggs Institute critical appraisal tool for randomized controlled trial (RCT) and quasi-experiment. After that, the study found was synthesized narratively. RESULTS: A total of 11.319 titles were identified, and seven studies met inclusion criteria with 3313 participants. Six studies were RCT studies, and one was a quasi-experimental study. The results of the narrative synthesis conducted on seven articles showed that health education by telenursing was effective in improving self-care ability, such as maintaining blood pressure, body mass index, hemoglobin A1c levels, fasting blood glucose, and low-density lipoprotein within normal limits. In addition, there was also an increase in physical activity, dietary compliance (consumption of fruits, vegetables and fish), control of salt intake, smoking, and alcohol cessation. The media used were phone calls and text messages. CONCLUSION: This review provides evidence that health education interventions effectively improve the self-care abilities of CAD patients with the media used are text messages and telephone calls.